LEAN MANUFACTURING - Enty Nur Hayati (Jurnal Ilmiah Dinamika Teknik, 2011)
Lean Manufacturing is an operational strategy oriented toward achieving the shortest possible cycle time by eliminating waste. It is derived from the Toyota Production System and its key thrust is to increase the value-added work by eliminating waste and reducing incidental work. The technique often decreases the time between a customer order and shipment, and it is designed to radically improve profitability, customer satisfaction, throughput time, and employee morale. The benefits generally are lower costs, higher quality, and shorter lead times.  The term "lean manufacturing" is coined to represent half the human effort in the company, half the manufacturing space, half the investment in tools, and half the engineering hours to develop a new product in half the time. Lean Manufacturing incorporates the use of Heijunka, level sequential flow, takt time, the heartbeat or pace of the production system, continuous flow manufacturing, cellular manufacturing, and pull production scheduling techniques such as Kanban.   Keywords: Lean Manufacture, Toyota Production System, Kanban